PHealth 2014: Proceedings of the 11th International Conference on Wearable Micro and Nano Technologies for Personalized Health, 11-13 June 2014, Vienna, Austria - Blobel, Bernd; Sauermann, Stefan; Mense, Alexander (Studies in health technology and informatics, 2014)
Microsystems, smart textiles, telemedicine, mobile computing, smart implants, sensor-controlled medical devices, and innovative sensor and actuator principles and techniques have become important enablers, not only for monitoring, diagnosis and treatment in both inpatient and outpatient care, but also for personalized, preventive, predictive participative systems medicine. This book contains the proceedings of pHealth 2014, the 11th in a series of successful international conferences on wearable or implantable micro and nano technologies for personalized medicine, held in Vienna, Austria, in J
Print version record
Keywords: Electronic books; Congress; Electronic books -- Conference papers and proceedings; Konferenzschrift; Biosensor; Medizintechnik; Nanotechnologie; Medizinische Informatik